2001
DOI: 10.1063/1.1375149
|View full text |Cite
|
Sign up to set email alerts
|

Charging and trapping of macroparticles in near-electrode regions of fluorocarbon plasmas with negative ions

Abstract: Charging and trapping of macroparticles in the near-electrode region of fluorocarbon etching plasmas with negative ions is considered. The equilibrium charge and forces on particles are computed as a function of the local position in the plasma presheath and sheath. The ionic composition of the plasma corresponds to the etching experiments in 2.45 GHz surface-wave sustained and 13.56 MHz inductively coupled C4F8+Ar plasmas. It is shown that despite negligible negative ion currents collected by the particles, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…It should be pointed out that high-quality Al x In 1−x N ternary alloys have recently been grown on the thick GaN buffer layers by metal organic chemical vapor deposition under In-rich conditions, however, the growth temperature is still high and remains [8] Eg(x) = 2.53x 2 − 6.92x + 6.28 [23] Eg(x) = 1.75 + 2.2x − 6.9x 2 + 9.1x 3 [28] 1.47 [29] 1.31 [31] Eg(x) = 0.66 + 0.81x + 4.38x 2 This work 2.41 in the range 750-810 • C [32]. It is believed that the quality of our Al x In 1−x N films can be possibly further improved by optimizing the growth processes including the optimal growth of the buffer and growth control of Al x In 1−x N films using effective low-temperature plasma-based tools [33,34].…”
Section: Resultsmentioning
confidence: 98%
“…It should be pointed out that high-quality Al x In 1−x N ternary alloys have recently been grown on the thick GaN buffer layers by metal organic chemical vapor deposition under In-rich conditions, however, the growth temperature is still high and remains [8] Eg(x) = 2.53x 2 − 6.92x + 6.28 [23] Eg(x) = 1.75 + 2.2x − 6.9x 2 + 9.1x 3 [28] 1.47 [29] 1.31 [31] Eg(x) = 0.66 + 0.81x + 4.38x 2 This work 2.41 in the range 750-810 • C [32]. It is believed that the quality of our Al x In 1−x N films can be possibly further improved by optimizing the growth processes including the optimal growth of the buffer and growth control of Al x In 1−x N films using effective low-temperature plasma-based tools [33,34].…”
Section: Resultsmentioning
confidence: 98%
“…Vladimirov et al 10 have studied ion-acoustic waves in a dust-contaminated plasmas. Charging and trapping of macroparticles in near electrode regions of fluorocarbon plasmas with negative ions has been studied by Ostrikov et al 11 Later, a self-consistent theory of linear ion-acoustic waves in complex laboratory plasmas containing dust grains and negative ions has been presented by Vladimirov et al 12 Sharma and Srivastava 13 have developed a model of ion beam driven ion-cyclotron waves in a cylindrical magnetized plasma with negative ions. It was found that the frequencies and the growth rate of both the unstable modes in the presence of negative and positive ions increase with the relative density of negative ions.…”
Section: Introductionmentioning
confidence: 98%
“…Probably, the best characterized systemswith respect to the formation of particles-are discharges operated in silane ͑SiH 4 ͒ 9,10 and in fluorocarbons such as CF 4 or C 2 F 6 . 11,12 The investigations on particle formation in silane and fluocarbon gases were highly motivated by their technological importance: 13 fluorocarbon plasmas are an important tool for the etching of microstructures, while discharges operated in silane are mainly used for the production of solar cells. Another class of gases used for the production of particles are hydrocarbons as C 2 H 2 or CH 4 .…”
Section: Introductionmentioning
confidence: 99%